Penatalaksanaan Fisioterapi Pada Kondisi frozen Shoulder Sinistra Akibat Capsulitas Adhesiva di RSUD Saras Husada Purworejo - FM, Ardiansyah; , Arif Pristianto, SSt.FT.,M.Fis (2015)
Background: Frozen Shoulder Capsilitis Adhesiva is a pathology that is characterized by pain, limitation of joint movement glenohumeralis either actively or passively without radiological changer. The limited nature of this condition characteristized by capsular pattern, wihich is charateristized by pain and movement more limited eksorotation of abduction as well as more limited than endorotationl. Objective: To study about physiotherapy management in reducing pain, increasing renge of motion, increase muscle strength and functional activity in the case of Frozen Shoulder capsulitis due adhesive using modalities Short Wave Deathermy, Manipulation Therapy and Therapiutic Exercise. Result: After therapy for six times the obtained result of the assessment in painful silence T:0 aT6:0, tenderness T1:5,8 a4.3, motion pain T1:9, 1 a T6:7,1, the assessment in range of motin S:T140-0-97 aT6:44-0-113, F: T1 63-0-39 a T6:88-0-55, R (F=0): T138-0-33 aT6:45-0-60, the assessment in abductor muscle strength T1: 3 - a T6: 4, Adductor R1:4- a 4 +, flexor T1:4- a T6:4+, extensor T1:4- a T6: 4+, endorotator T1: 4- a 4+, flexor T1: 4- a T6:4+ extenser T1:4- a T6: 4+, endorotator T1: 4- a T6: 4, exorotator T1:4- a T6: 4, the assessment in functional activity T1:91.25% a T6: 52,5%. Conclusion: Short Wave Deathermy can reduce pain, manipulation therapy and therapeutic exercise can improve range of motin, increase muscle strength and functional activity in condition coused by Frozen Shoudr sinistra capsulitis adhesive.